Понятие некоммерческой организации и ее место в системе гражданского права - Aitimov, B.Zh.; Dussipov, Ye.Sh.; Seriev, B.A. (Bulletin of the Karaganda University “Law Series”, 2021)
In the scientific article, the concept of «non-profit organization», formed in the scientific community, is investigated in comparison with practical examples, foreign theoretical ideas. At the moment, it is important to reconsider the concept of «non-profit organization». Obviously, the main reason is the formation and development of the Kazakh experience of local self-government by increasing the political, economic and social activity of citizens, as a result of which local problems would be solved using the population's own potential. However, there is no scientific and theoretical understanding of the concept «non-profit organization» in terms of its main goals. This, in turn, will not allow to improve the domestic legislation on non-profit organizations. One of the main reasons for the underdevelopment of legislation in this area without the involvement of international and foreign organizations can be seen in the imperfection of state policy aimed at the formation and development of civil society. We believe that this is the result of the work of government agencies interested in the development of this industry. The aim of the study is to define the concept of «non-profit organization» under the civil legislation of the Republic of Kazakhstan and its place in civil law, at the state and public levels. In addition to statistical, analytical, synthesizing, comparative legal, linguistic research methods, the article uses methods such as the assessment of real social activities, legal audit in the study of their practical development. As a result of the study, it was suggested that the existing criteria for distinguishing between commercial and non-commercial organizations are hardly applicable, and, therefore, there is a need to create new criteria for their separation, such as «public benefit», etc.